THE DYNAMIC OF INDICATORS OF LIPID PEROXIDATION AND ANTIOXIDANT PROTECTION STATUS IN PATIENTS WITH POLYTRAUMA AND ALCOHOL WITHDRAWAL SYNDROME COMPLICATED BY ALCOHOL DELIRIUM (World Science, 2021)
Injuries are one of the leading causes of death and disability in the world. It is known that from 25% to 85% of patients are in a state of alcohol intoxication during hospitalization in the polytrauma department, 5-20% of them develop alcoholic delirium as a complication of alcohol withdrawal.The aim of the study was to analyze the indicators of lipid peroxidation and antioxidant protection in patients with moderate polytrauma and with a state of alcohol withdrawal complicated by alcoholic delirium, depending on the method of sedation. Material and research methods. The study included 80 patients with polysystemic trauma of moderate severity and with a state of alcohol withdrawal complicated by alcoholic delirium. The median age was 45 years [39-54]. Patients in Group 1 (n = 40) were given dexmedetomidine as a sedation method, and in Group 2 (n = 40) they used sedation with diazepam according to the symptom-trigger protocol. The content of the main indicators of the oxidative system was determined in the serum of patients: active products of thiobarbituric acid, diene conjugates, 8-isoprostane to assess the intensity of lipid peroxidation. The state of the antioxidant system was assessed by the content of superoxide dismutase, catalase, glutathione peroxidase. Conclusions. The use of dexmedetomidine for sedation of patients with alcohol withdrawal and alcoholic delirium and polytrauma reduces the manifestations of lipid peroxidation due to faster recovery of enzyme systems of antioxidant protection.